The methods of inversion and the maximum likelihood estimation in acoustic tests of industrial sources in the environment - Stryczniewicz, L. (Archives of Acoustics, 2006)
Determining an acoustic model of a factory is a topic connected to the noise sources identificationin the factory, their localization and acoustic parameters. In order to determine thesource parameters correctly, it is necessary to use the whole available knowledge accessed inacoustic measurements and the knowledge obtained a priori (e.g. on the basis of producers’catalogues of equipment). To solve this problem the method of the acoustic inversion was usedwith the maximum likelihood estimation. The biggest advantage of this method is the possibilityto use the information concerning accuracy of the determined a priori sound power ofnoise sources and indicating the importance of the sound pressure level values in measurementareas. The theoretical assumptions of the method, its adjustment to the industrial conditionsas well as tosome computer simulations are presented in the paper.